“Grande” arte para quem faz parte: atuação da sociedade de cultura artística Brasílio Itiberê em Ponta Grossa (PR) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2021)
This research aims to understand the cultural and artistic influences, as well as the consequent production of meanings, that the Sociedade de Cultura Artística Brasílio Itiberê (SCABI), caused in the municipality of Ponta Grossa - PR. By the initiative of intellectuals, this institution began to operate in 1945, in Curitiba, capital of the state of Paraná, in order to foster the classical culture in that city. A few years later, in 1949, SCABI created a branch in Ponta Grossa, a city that at that time was experiencing a moment of cultural passivity. In this way, they were brought to the city in regular artistic shows, lyrical singers, orchestras, instrumentalists, dancers, of national and international renown; to present themselves to a limited audience of associates, until 1972. To better understand the performance of this society in Ponta Grossa, which has still been little studied, and to evaluate the multiple meanings that artistic presentations have acquired, the research seeks to unveil the social network of which were responsible agents, understood as intellectual cultural mediators. As main sources, we used administrative reports, presentation programs, and newspaper clippings from the newspaper library that make up the SCABI collection present in the Centro de Documentação e Pesquisa da Casa da Memória of the Fundação Cultural de Curitiba; and also, the narratives that intertwine time, society and space about the SCABI branch, present in the newspapers Diário dos Campos and Jornal da Manhã. The methodological approach was carried out through an exploratory descriptive analysis of this documentation, especially from the 1950s - a period in which the institution promoted more presentations, and which has more sources; making it possible to understand the unique existence of SCABI in the way of systematizing and reaffirming the sociability of the network in which the intellectual cultural mediators themselves were part. Also, there was a demonstration and contextualization of the gradual decrease of the presentations, until reaching the end of the institution; and pointing out some of the influences that the institution has reflected and still reflects in society, showing in that way, that the symbolic goods mediated and legitimized by SCABI are still popular in Ponta Grossa.
Keywords: Sociedade de Cultura Artística Brasílio Itiberê (SCABI); SCABI Ponta Grossa; Intelectuais mediadores (as) culturais; Arte erudita; Sociedade de Cultura Artística Brasílio Itiberê (SCABI); SCABI Ponta Grossa; Intellectual cultural mediators; Classical Art; CNPQ::CIENCIAS HUMANAS::HISTORIA